1986
DOI: 10.1139/z86-085
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between molecular weight and antifreeze polypeptide activity in marine fish

Abstract: Previous studies have established that the capacity of the glycopeptide antifreezes to depress the freezing temperature of aqueous solutions is positively correlated with molecular weight. The present study was carried out to determine whether a similar correlation existed within the antifreeze peptides. Two approaches were used. Initially, the antifreeze activity (thermal hysteresis) curves of antifreeze peptides from winter flounder, Pseudopleuronectes americanus (molecular weight, 3300), shorthorn sculpin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 2 publications
2
32
0
Order By: Relevance
“…Activity measurement requires very high concentrations of AFP. In addition, the activity of fish AFPs increases in a nonlinear fashion with protein concentration forming a hyperbolic curve (Kao et al, 1986). This study does, however, provide a clear illustration of the metal ion requirements of the AFP when present at physiological concentrations in herring blood.…”
Section: Ca 2ϩ -Dependent Antifreeze Proteinsmentioning
confidence: 75%
“…Activity measurement requires very high concentrations of AFP. In addition, the activity of fish AFPs increases in a nonlinear fashion with protein concentration forming a hyperbolic curve (Kao et al, 1986). This study does, however, provide a clear illustration of the metal ion requirements of the AFP when present at physiological concentrations in herring blood.…”
Section: Ca 2ϩ -Dependent Antifreeze Proteinsmentioning
confidence: 75%
“…The polyacrylamide gel electrophoresis showed that the AFGPs are degraded into many sub-sizes during the digestion process. As pointed out in other studies, the size composition of AFGP have crucial influence on the antifreeze activity (Ahlgren and DeVries, 1984;Kao et al, 1986;Osuga et al, 1978;Schrag et al, 1982). Thus, a possible explanation for the high antifreeze activity can be the combination of many sub-sizes of AFGP and the fact that the concentration of AFGP increases in the intestine due to water uptake by the gut wall (O'Grady et al, 1982b).…”
Section: Discussionmentioning
confidence: 86%
“…The AFGPs appear in at least eight sizes with molecular masses ranging between 2.6-33.7·kDa, but recent high resolution gradient gels show at least 15 molecular isoforms (Chen et al, 1997). The ) have the greatest antifreeze activity (Kao et al, 1986;Osuga et al, 1978;Schrag et al, 1982), whereas the smaller AFGP6-8 (7.9-2.6·kDa) only exhibit up to a third of the antifreeze activity of AFGP1-5 (Kao et al, 1986;Osuga et al, 1978;Schrag et al, 1982). Furthermore, it has been shown that the antifreeze activity strongly depends on the AFGP concentration (O'Grady et al, 1982a).…”
mentioning
confidence: 99%
“…The partially purified AFP were resolved into individual components by reversephase high-performance liquid chromatography (HPLC) using a Waters pBondapak CIS column (0.78 x 30 cm) with an acetonitrile gradient in 0.05% trifluoroacetic acid. Antifreeze activity of the components, as determined by thermal hysteresis values [17], was measured by a nanolitre osmometer (Clifton Technical Physics, Hartford, NY, USA).…”
Section: Dna Sequencingmentioning
confidence: 99%